2015
DOI: 10.1128/jvi.03483-14
|View full text |Cite
|
Sign up to set email alerts
|

Effective Lethal Mutagenesis of Influenza Virus by Three Nucleoside Analogs

Abstract: Lethal mutagenesis is a broad-spectrum antiviral strategy that exploits the high mutation rate and low mutational tolerance of many RNA viruses. This approach uses mutagenic drugs to increase viral mutation rates and burden viral populations with mutations that reduce the number of infectious progeny. We investigated the effectiveness of lethal mutagenesis as a strategy against influenza virus using three nucleoside analogs, ribavirin, 5-azacytidine, and 5-fluorouracil. All three drugs were active against a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 66 publications
(109 reference statements)
2
80
0
2
Order By: Relevance
“…Second, the presence of a natural ribose implies that in theory, chain elongation is possible in the case that T-705-RTP or RBV-TP is used as an alternative substrate by the influenza virus polymerase. These two factors could explain recent observations that cell culture passaging of influenza virus in the presence of T-705 (25) or ribavirin (26,27) leads to virus mutagenesis; this mutagenic effect was also seen in influenza virus-infected mice receiving T-705 therapy (28). Enzymatic studies showed that influenza virus polymerase recognizes T-705-RTP as an alternative substrate versus GTP and ATP (29,30).…”
mentioning
confidence: 86%
“…Second, the presence of a natural ribose implies that in theory, chain elongation is possible in the case that T-705-RTP or RBV-TP is used as an alternative substrate by the influenza virus polymerase. These two factors could explain recent observations that cell culture passaging of influenza virus in the presence of T-705 (25) or ribavirin (26,27) leads to virus mutagenesis; this mutagenic effect was also seen in influenza virus-infected mice receiving T-705 therapy (28). Enzymatic studies showed that influenza virus polymerase recognizes T-705-RTP as an alternative substrate versus GTP and ATP (29,30).…”
mentioning
confidence: 86%
“…Substitutions that confer resistance to polymerase inhibitors would be expected to significantly decrease virus fitness (74,75). Serial passage in cells with various nucleoside analogues, such as ribavirin, T-705, 5-azacytidine, and 5-fluorou-racil, often fails to yield specific substitutions in the polymerase proteins because of the lethal mutagenesis mechanism of these compounds (76)(77)(78). However, this mechanism is different from that employed by RO-7; it is unknown to what degree the viral PA protein can escape from RO-7 drug pressure and still retain suitable endonuclease activity.…”
Section: Discussionmentioning
confidence: 99%
“…In short, we used overlap PCR mutagenesis to introduce the following mutations: HA, T1583G; HA, G1006T; HA, G542T; M, T861G; M, A541C; NA, G1168T; NA, C454T; NP, A454C; NP, A1160T; NS, G227T; NS, A809G; PA, T964G; PA, T237A; PA, A1358T; PB1, G599A; PB1, G1764T; PB1, T1288A; PB2, A1854G; PB2, A440T; and PB2, A1167T. Viruses were rescued from transfected cells as described previously (38).…”
Section: Methodsmentioning
confidence: 99%
“…Madin-Darby canine kidney cells were provided by Arnold S. Monto (University of Michigan School of Public Health) and were maintained in Dulbecco's modified Eagle medium (DMEM) (Invitrogen) with 10% fetal bovine serum (Gibco and HyClone), 25 mM HEPES (Invitrogen), and 0.1875% bovine serum albumin (Life Technologies). Influenza A/WSN/33(H1N1) virus was rescued from transfected cells using an 8-plasmid reverse genetic system containing each genomic segment (pHW181 to -188), a kind gift from Robert Webster (St. Jude's Children's Research Hospital) (37,38). A biological clone of influenza A/Puerto Rico/8/1934(H1N1) virus was obtained from the ATCC (VR-1469), and the genomic segments were cloned into the pHW2000 reversegenetic system (38).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation